2018
DOI: 10.1038/s41419-018-0596-8
|View full text |Cite
|
Sign up to set email alerts
|

Grail is involved in adipocyte differentiation and diet-induced obesity

Abstract: Grail is a crucial regulator of various biological processes, including the development of T-cell anergy, antiviral innate immune response, and cancer. However, the role of Grail in adipogenesis and obesity remains unclear. Here, we demonstrated that Grail knockdown in vitro leads to a decrease in PPARγ expression, resulting in adipogenesis inhibition. However, Grail overexpression induced the same effects. Grail was shown to interact with PPARγ, targeting it for degradation and modulating its adipogenic activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 40 publications
1
19
0
Order By: Relevance
“…Similarly, KRT18 has been invoked as a biomarker for obesity-related hepatic dysfunction in obese adolescents [58], so our finding of its change in this model would support its use as a preclinical model of human pubertal obesity. Functional neighborhood analyses revealed ubiquitin ligases DTX4 and DTX1 and the methyltransferase SUV420h2 as potential nodes of interest, as previously reported data on adipocyte differentiation and dietinduced obesity reveals [59,60]. These results reinforce the usefulness of PBMC transcriptome analyses in this model.…”
Section: Discussionsupporting
confidence: 83%
“…Similarly, KRT18 has been invoked as a biomarker for obesity-related hepatic dysfunction in obese adolescents [58], so our finding of its change in this model would support its use as a preclinical model of human pubertal obesity. Functional neighborhood analyses revealed ubiquitin ligases DTX4 and DTX1 and the methyltransferase SUV420h2 as potential nodes of interest, as previously reported data on adipocyte differentiation and dietinduced obesity reveals [59,60]. These results reinforce the usefulness of PBMC transcriptome analyses in this model.…”
Section: Discussionsupporting
confidence: 83%
“…All experimental animal procedures were approved by the Institutional Animal Care and Use Committee (ref no: IACUC-AN106-08) of the Preventive Medicine Institute, National Defense Medical Center, Taiwan. The Grail KO mice were generated by the Transgenic Mouse Models Core (Taipei, Taiwan) using CRISPR-Cas9 technology, which induced an NHEJ-mediated deletion in Grail exon 1, resulting in the removal of the first start codon, and the KO mice were generated on a C57BL/6 J background 27 . Six-week-old mice were used and randomly selected for the experimental and control groups.…”
Section: Methodsmentioning
confidence: 99%
“…Our previous work also shows that Grail can regulate p53-mediated cell cycle arrest and apoptosis in response to DNA damage 26 . There is also evidence that Grail plays a crucial role in adipogenesis and diet induced obesity 27 . The dysregulation of Grail has been linked to ulcerative colitis, a chronic inflammatory disease of the gastrointestinal tract 28 .…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, strategies targeting MDM2 should be cautiously employed, considering that MDM2 plays both oncogenic and tumor-suppressive roles via degrading wt and mtp53, respectively. RNF128 encodes two isoforms of the ring finger protein RNF128 that was characterized as a crucial regulator of T cell function, cytokine production, and nutrient metabolism through in vitro and in vivo studies [121][122][123]. A recent study demonstrated that RNF128, namely Grail, which is also transcriptionally induced by wtp53, can in turn physically and functionally interact with the N-terminus of wtp53 to induce its proteasomal degradation, resulting in the inhibition of cancer cell apoptosis [86].…”
Section: Ring-finger E3 Ligasesmentioning
confidence: 99%
“…Interestingly, RNF128 seemed to modulate p53 transcriptional activity and determine cell fate by differentially regulating cell cycle and apoptotic gene expression, as loss of RNF128 expression induced p21-dependent cell cycle arrest, but not p53-dependent apoptosis [86], revealing an unique regulatory mode for controlling p53 activity. On the contrary, it has also been reported RNF128 encodes two isoforms of the ring finger protein RNF128 that was characterized as a crucial regulator of T cell function, cytokine production, and nutrient metabolism through in vitro and in vivo studies [121][122][123]. A recent study demonstrated that RNF128, namely Grail, which is also transcriptionally induced by wtp53, can in turn physically and functionally interact with the N-terminus of wtp53 to induce its proteasomal degradation, resulting in the inhibition of cancer cell apoptosis [86].…”
Section: Ring-finger E3 Ligasesmentioning
confidence: 99%